2020
DOI: 10.1080/17453674.2020.1779516
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the mechanical hip–knee–ankle angle accurately from standard knee radiographs: a cross-validation experiment in 100 patients

Abstract: Background and purpose — Being able to predict the hip–knee–ankle angle (HKAA) from standard knee radiographs allows studies on malalignment in cohorts lacking full-limb radiography. We aimed to develop an automated image analysis pipeline to measure the femoro-tibial angle (FTA) from standard knee radiographs and test various FTA definitions to predict the HKAA. Patients and methods — We included 110 pairs of standard knee and full-limb radiographs. Automatic search algorithms found anatomic landma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…This is the rst study to our knowledge to present a fully automatic method for measuring coronal knee alignment using knee-only PA radiographs, demonstrating high accuracy for FTA (MAE: 0.8°) and outperforming state-of-the-art 11 for HKA (MAE: 1.7°). This nding is particularly impressive considering no restrictions were imposed on the training dataset and no anatomical annotation was required.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This is the rst study to our knowledge to present a fully automatic method for measuring coronal knee alignment using knee-only PA radiographs, demonstrating high accuracy for FTA (MAE: 0.8°) and outperforming state-of-the-art 11 for HKA (MAE: 1.7°). This nding is particularly impressive considering no restrictions were imposed on the training dataset and no anatomical annotation was required.…”
Section: Discussionmentioning
confidence: 93%
“…Whilst HKA is the better measure, many centres choose to use only FTA for preop planning or postop follow-up as it is cheaper and more convenient. Enabling HKA measurement from knee-only radiographs would thus be of great clinical use: 11 producing the gold-standard measure with reduced cost and radiation exposure, providing additional information for knee arthroplasty planning and follow-up for surgeons who do not routinely have access to full-limb radiographs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed the agreement between the FTA on SKR and WLR in the WB position was greater than that in the NWB position (ICC 0.878 vs. 0.657). Additionally, the FTA was often measured on SKR using lines drawn from the knee to a point approximately 10 cm proximal to the center of the knee (17); however, the location the point for the bone shaft also might alter the correlation of FTA to HKA. Sheey's et al (11) compared different versions of FTA and HKA using different reference points and concluded that using shorter FTA shaft lengths to evaluate HKA modestly weakened the correlation of the 2 measurements.…”
Section: Discussionmentioning
confidence: 99%
“…FTA SKR was defined as the intersecting angle of the femoral and tibial anatomical axis on SKR. The measurements were performed using a general technique and validated by Gielis et al (17). To have a better reflection of femoral and tibial anatomical variations (18), we selected the more distant reference points of the femur and tibia (those which were closest to the edge of the image).…”
Section: Alignment Measurementsmentioning
confidence: 99%